Google App Script untuk Pengembangan Sistem Infromasi Laboratorium - Haryadina Putra, Bima Al Fatih; Dirgahayu, Raden Teduh (Universitas Multi Data Palembang, 2025)
Efficient laboratory management is essential to support academic activities at the Islamic University of Indonesia (UII). The Informatics Department Laboratory at UII faces challenges with an unintegrated room booking and inventory system, complicating resource management for administrators and users. This study aims to develop a laboratory information system based on Google Apps Script to facilitate automated room bookings integrated with Google Workspace services such as Google Calendar, Google Spreadsheets, and Google Sites. The research employs the Waterfall model, encompassing requirements analysis, system design, development, and testing. The results demonstrate that the developed system successfully automates the room booking process, provides real-time schedule access, and accelerates the approval process through email notifications. Functional testing confirmed that the system operates according to specifications and meets user needs. The conclusion of this study is that the laboratory information system based on Google Apps Script effectively enhances the efficiency of room booking management in the Informatics Faculty at UII. However, the system has limitations related to dependency on Google services, scalability, and feature flexibility, which require further development.